Analyzing Factors of Sustainable Development of Organizations Working in Service Sector - E. G. Neofitu (Вестник Российского экономического университета имени Г. В. Плеханова)
Sustainable development in the service sector means a concept of development, which assumes creation of adequate conditions for meeting customer needs. It embraces economic, social, ecological, cultural and technological aspects that should be taken into account for service rendering. The article studies key groups of factors affecting the sustainable development of the organization working in the service sector. Social responsibility implies that services shall take into due consideration social needs and interests, as well as accessibility for all groups of the population. Organizational and economic sustainability means economic efficiency of service rendering processes to ensure sales and profit of the company and free cash flow. Services shall be ecologically sustainable and be harmless for the environment. Cultural factors are also very important, as they support values and comfortable working conditions and interaction with customers, partners and counterparts. Companies should do their best to improve the quality of services and introduce advanced digital technologies and innovation. It will give them an opportunity to be competitive and meet changing needs of their customers. The notion of dynamic sustainability of the organization working in the service sector was put forward by the author.